Strategies to Increase Farmers' Financial Inclusion - Yuwono, Minto; Nurmalina, Rita, Prof, Dr.Ir, MS; Suharjo, Budi, Dr.Ir. MS; Sanim, Bunasor, Prof, Dr.Ir, MSc (The South East Asian Journal of Management, 2016)
This research aims to determine the level of interest by farmers in using the services of formal financial institutions, especially digital financial services (DFS). The methods of the research were descriptive statistics and SEM analysis. The majority of respondents (50%) farmed an average area of land less than 0.5 hectares, 26% of respondents an average of 0.75-1 hectares and 24% of respondents an average of 0.5-0.75 hectares of land. Based on the status of land ownership, as many as 76% of respondents owned the property itself, 19% had a “lease” arrangement and 5% used state owned “arable”land. A total of 27% of the farmers were interested in using DFS while 34% were not. The lack of intereset was due to practical uses, enjoyment of cash and lack of knowledge. The reason for interest in DFS included practicality, speed, and security of use. Results from the SEM model indicate a significant and positive influence of Access to Usage, significant and negative influence of DFS to Access, significant and positive influence of DFS to Interest, significant and positive of Interest to Desire, and a significant and positive Desire to Access.